2015
DOI: 10.3389/fimmu.2015.00083
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory role of platelets via their TLRs and Siglec receptors

Abstract: Platelets are non-nucleated cells that play central roles in the processes of hemostasis, innate immunity, and inflammation; however, several reports show that these distinct functions are more closely linked than initially thought. Platelets express numerous receptors and contain hundreds of secretory products. These receptors and secretory products are instrumental to the platelet functional responses. The capacity of platelets to secrete copious amounts of cytokines, chemokines, and related molecules appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
171
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 160 publications
1
171
3
4
Order By: Relevance
“…4,47 Indeed, recent investigations have demonstrated that platelets express the TLR1 through TLR4 and TLR6 through TLR9 and that at least TLR2, TLR4, and TLR9 are functional receptors in platelets facilitating antigen recognition and innate responses. 6,48 Thus platelets can recognize antigens broadly shared by pathogens but distinguishable from host molecules, which are collectively referred to as pathogen-associated molecule patterns, and in the case of TLR2, TLR4, and TLR9, platelets might recognize diacylated and triacylated lipopeptides, LPS, and bacterial or viral DNA, respectively. 48 One functional example of this is when platelets activated by LPS through TLR4 receptors promote neutrophil extracellular trap formation in response to bacteria.…”
Section: Platelet Interactions With Immune Cells and Effects On Allermentioning
confidence: 99%
See 1 more Smart Citation
“…4,47 Indeed, recent investigations have demonstrated that platelets express the TLR1 through TLR4 and TLR6 through TLR9 and that at least TLR2, TLR4, and TLR9 are functional receptors in platelets facilitating antigen recognition and innate responses. 6,48 Thus platelets can recognize antigens broadly shared by pathogens but distinguishable from host molecules, which are collectively referred to as pathogen-associated molecule patterns, and in the case of TLR2, TLR4, and TLR9, platelets might recognize diacylated and triacylated lipopeptides, LPS, and bacterial or viral DNA, respectively. 48 One functional example of this is when platelets activated by LPS through TLR4 receptors promote neutrophil extracellular trap formation in response to bacteria.…”
Section: Platelet Interactions With Immune Cells and Effects On Allermentioning
confidence: 99%
“…6,48 Thus platelets can recognize antigens broadly shared by pathogens but distinguishable from host molecules, which are collectively referred to as pathogen-associated molecule patterns, and in the case of TLR2, TLR4, and TLR9, platelets might recognize diacylated and triacylated lipopeptides, LPS, and bacterial or viral DNA, respectively. 48 One functional example of this is when platelets activated by LPS through TLR4 receptors promote neutrophil extracellular trap formation in response to bacteria. 49,50 The role of TLRs in asthma and allergy is reviewed elsewhere, 51 yet the significance of TLRs expressed on platelets in the processes leading to sensitization to allergens remains unknown.…”
Section: Platelet Interactions With Immune Cells and Effects On Allermentioning
confidence: 99%
“…В 2004 г. на тромбоцитах впервые выявлены Toll-подобные рецепторы (TLR), что существенно продвинуло представление о них как о клетках, вовлеченных в распознавание патогенов и связан-ного с ними воспаления [11]. Показано наличие функциональных TLR2, TLR4, TLR7 и TLR9 [12].…”
Section: тромбоциты как сенсоры бактерийunclassified
“…Platelet transfusion also has the inherent risk of transmission of blood-borne diseases; polymorphism of human platelet antigen (HPA) and human leukocyte antigen (HLA) after transfusion can also lead to complications such as transfusion refractoriness, which is the failure to achieve the desired level of platelets following transfusion, and von Willebrand's disease. 22,43,45 Platelet transfusion can also be potentially pro-inflammatory or highly immunogenic; recipients of donated platelets run the risk of alloimmunization, exposure to the transmission of infections, graft-vs-host disease, or transfusion-related immunosuppression, which could increase their vulnerability to a host of other harmful pathogens. 20,46 Therefore, the short shelf life of natural platelets poses a considerable restriction on the practicality of platelet transfusion therapy.…”
Section: Platelet-mimetic Strategies and Technologies Natural Platelementioning
confidence: 99%
“…19 As part of the innate immune system, platelets have a significant role in the inflammatory response at sites of injury and/or disease through activation of and close interaction with leukocytes (regulated by cathepsin G), secretion of chemokines and cytokines that attract other immune cells, and through additional mechanisms that influence the body's adaptive immunity. 10,[20][21][22][23] Tissue inflammation and healing are further modulated by protease-activated receptors (PARs) found on platelet surfaces; these PARs stimulate the release of alpha granules, which contain various growth factors and angiogenic factors that aid in tissue repair. 24,25 Many glycoproteins found on the platelet surface membrane, such as CD55 and CD59, are a part of the complement system, which eliminates particulate invaders by providing recognition mechanisms for phagocytes that can then clear invaders from the body via phagocytosis.…”
Section: Platelets In Coagulation and Hemostasismentioning
confidence: 99%